Phylogeography and Genetic Diversity in a Southern North American Desert: Agave kerchovei From the Tehuacán-Cuicatlán Valley, Mexico - Aguirre-Planter, Erika; Parra-Leyva, J. Gilberto; Ramírez-Barahona, Santiago; Scheinvar, Enrique; Lira-Saade, Rafael; Eguiarte, Luis E. (Frontiers in Plant Science, 2020)
The Tehuacán-Cuicatlán Valley, located at the southeast of the state of Puebla and the northeast of the state of Oaxaca in Central Mexico, south of the Trans-Mexican Volcanic Belt (TMVB), is of particular interest for understanding the evolutionary dynamics of arid and semi-arid environments. Studying in detail the phylogeography, environmental history and population genetics of representative species will hopefully shed light on the evolutionary and ecological dynamics that generated the tremendous biodiversity and endemism of this important region in Mexico. We sequenced three non-coding regions of chloroplast genome of Agave kerchovei, a representative species of the Tehuacán Valley, generating 2,188 bp from 128 individuals sampled from eight populations throughout the species range. We used this data set to (i) characterise the levels of genetic diversity and genetic structure in A. kerchovei; (ii) predict the distribution of A. kerchovei for the present day, and to reconstruct the past geographical history of the species by constructing ecological niche models (ENM); and (iii) compare the levels of diversity in this species with those estimated for the widely distributed Agave lechuguilla. Agave kerchovei has high levels of total chloroplast genetic variation (Hd = 0.718), especially considering that it is a species with a very restricted distribution. However, intrapopulation diversity is low (zero in some populations), and genetic structure is high (FST = 0.928, GST = 0.824), which can be expected for endemic species with isolated populations. Our data suggest that Pleistocene glacial cycles have played an important role in the distribution of A. kerchovei, where the climatic variability of the region -- likely associated with its topographic complexity -- had a significant effect on the levels of genetic diversity and population dynamics, while the potential distribution of the species seems to be stable since the middle Holocene (6 kya). We conclude that in A. kerchovei there is a core group of populations in the Tehuacán Valley, and peripheric populations that appear to be evolving independently and thus the species in fundamentally an endemic species from the Tehuacán Valley while the populations outside the Valley appear to be in the process of incipient speciation.